Violent loves and consuming passions in the work of Simon Boulerice - Bourdeau, Loic (Ondina - Ondine, 2021)
This contribution provides a close reading of Quebec author Simon Boulerice’s Les Jérémiades (2009), Javotte(2012), and L’Enfant mascara (2016) in an attempt to show how emotions and feelings are articulated, how adolescence is depicted, and how these texts are queer, that is, transgressive and transformative. By exploring topics such as love, hatred, sexual desire, and angst, Boulerice gives a voice to marginal characters who are usually non-existent or silenced. In particular, this work looks at the use of confessions, the rewriting of the fairytale, the predominance of bodies, and the questioning of social norms.Keywords: Quebec, queer, bodies, youth, emotions